A two-dimensional mathematical model investigation of the hydrodynamics and sediment transport of Saldanha Bay and Langebaan Lagoon - Wiese, Michael-John Barnardo (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScEng)--Stellenbosch University, 2013.